2002
DOI: 10.1038/nature721
|View full text |Cite
|
Sign up to set email alerts
|

Crumbs, the Drosophila homologue of human CRB1/RP12, is essential for photoreceptor morphogenesis

Abstract: The apical transmembrane protein Crumbs is a central regulator of epithelial apical-basal polarity in Drosophila. Loss-of-function mutations in the human homologue of Crumbs, CRB1 (RP12), cause recessive retinal dystrophies, including retinitis pigmentosa. Here we show that Crumbs and CRB1 localize to corresponding subdomains of the photoreceptor apical plasma membrane: the stalk of the Drosophila photoreceptor and the inner segment of mammalian photoreceptors. These subdomains support the morphogenesis and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
530
7
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(580 citation statements)
references
References 40 publications
41
530
7
2
Order By: Relevance
“…Here, we demonstrated that removal of CRB2 from either Müller glial or photoreceptors has similar effect on the apical complexes. This is partially in consonance with observations in PALS1 mutant mice (31,32), and consistent with the epithelial polarity and adhesion defects seen in both the Drosophila Crb mutant and the zebrafish Crb2a (ome) mutant (12,35,36). Short-term depletion of CRB2 in the adult retinas demonstrated that CRB2 is required for maintenance of the retinal structure.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Here, we demonstrated that removal of CRB2 from either Müller glial or photoreceptors has similar effect on the apical complexes. This is partially in consonance with observations in PALS1 mutant mice (31,32), and consistent with the epithelial polarity and adhesion defects seen in both the Drosophila Crb mutant and the zebrafish Crb2a (ome) mutant (12,35,36). Short-term depletion of CRB2 in the adult retinas demonstrated that CRB2 is required for maintenance of the retinal structure.…”
Section: Discussionsupporting
confidence: 73%
“…The Crumbs proteins are associated through PALS1 with PATJ or MUPP1, forming the core of the Crumbs complex (5 -10). In the developing and adult mouse retina, the apical Crumbs complex resides at the subapical region adjacent to the adherens junctions between the retinal progenitor cells (11) or between the photoreceptors and Müller glial cells (9,12). However, in the adult mouse retina, while CRB2 protein is present in both photoreceptor and Müller glial cells, CRB1 is detected only in Müller glial cells (13).…”
Section: Introductionmentioning
confidence: 89%
“…Important cellular processes involve cell protrusions, including nutrient resorption (Louvard et al, 1992), mechanosensing (Frolenkov et al, 2004), photosensing (Corbeil et al, 2001;Pellikka et al, 2002), establishment of cell adhesion (Vasioukhin et al, 2000), cell migration (Fulga and Rorth, 2002), fusion of epithelial sheets (Jacinto et al, 2000;MartinBlanco et al, 2000), wound healing (Wood et al, 2002), axon guidance (Ritzenthaler et al, 2000), and cell-tocell communication (reviewed in Rorth, 2003). Intercellular communication is important for the growth and patterning of tissues and organs and cell protrusions may mediate this communication by one of several mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Or, il existe chez les mammifères une structure jonctionnelle de type ZA, entre les photorécepteurs, et entre ces photorécepteurs et les cellules gliales de Müller. La protéine CRB1, accumulée dans cette structure, pourrait jouer un rôle dans l'organisation de ces jonctions [38]. Cela est confirmé par l'observation que ces jonctions sont perturbées dans la lignée de souris rd8 qui possède une mutation dans le gène CRB1 [39].…”
Section: Mécanismes Potentiels Des Maladies De La Rétine Dues à Des Munclassified
“…Cette fonction pourrait être portée par le domaine extracellulaire de CRB1, car les mutations responsables des RP12 ou des LCA concernent ce domaine [3]. L'analyse de clones déficients en crb dans l'oeil de drosophile a montré que le domaine cytoplasmique de Crumbs est essentiel pour la formation des ZA et de la tige des photorécepteurs, tandis que son domaine extracellulaire est important pour l'élongation des rhabdomères, l'équivalent du segment externe des photorécep-teurs de mammifères [38,40]. Ce domaine extracellulaire de la protéine crumbs protège également la rétine de la dégénéres-cence progressive induite par la lumière [41], en favorisant la survie des photorécepteurs.…”
Section: Mécanismes Potentiels Des Maladies De La Rétine Dues à Des Munclassified